DIFFERENCES OF HERBAL AND NON-HERBAL TOOTHPASTE AGAINST DECREASING PLAQUE INDEX OF ADOLESCENT WOMEN - Siti Almira Rahma; R. Harry Dharmawan Setyawardhana; Nurdiana Dewi (FKG Unlam, 2023)
Background: Women had better dental and oral health than men because women had better fine motor skills and manual dexterity than men. Dental and oral health problems commonly found in adolescents were caused by plaque. Plaque is a soft layer tightly attached to the tooth’s surface. Plaque could be cleaned mechanically and chemically by brushing teeth using toothpaste. Toothpaste was divided into two types, namely herbal and non-herbal toothpaste which had ingredients that were efficacious for dental health. Purpose: Analyzing the differences in the effectiveness of herbal and non-herbal toothpaste against decreasing plaque index in adolescent women around 11-19 years at the Aisyiah Hikmah Zam-Zam Orphanage and Harapan Ibu Orphanage, Banjarmasin. Methods: This study used the true experimental method with a pre-and post-test control group design, using simple random sampling. Result: The Wilcoxon test in the herbal toothpaste group obtained a significant value of 0.001 (<0.05) which meant that there was a significant difference between the plaque index before and after using herbal toothpaste, while in the non-herbal toothpaste group a significant value of 0.124 (>0.05) which meant that there was no significant difference between the plaque index before and after using non-herbal toothpaste. The significance of the Mann-Whitney test in the herbal and non-herbal toothpaste group was 0.037 (<0.05), which meant that there were differences in the effectiveness of herbal and non-herbal toothpaste in adolescent women. Conclusion: Toothpaste with herbal content was more effective in lowering plaque index in adolescent women compared to non-herbal toothpaste. Keywords: Adolescent, Herbal Toothpaste, Nonherbal Toothpaste, Plaque Index